2017
DOI: 10.1155/2017/3759287
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress as a Physiological Pain Response in Full‐Term Newborns

Abstract: This research paper aims to investigate if oxidative stress biomarkers increase after a painful procedure in term newborns and if nonpharmacological approaches, or sex, influence pain degree, and the subsequent OS. 83 healthy term newborns were enrolled to receive 10% oral glucose or sensorial saturation (SS) for analgesia during heel prick (HP). The ABC scale was used to score the pain. Advanced oxidation protein products (AOPP) and total hydroperoxides (TH) as biomarkers of OS were measured at the beginning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 39 publications
0
17
0
8
Order By: Relevance
“…The mechanism involved in these results could be mediated by its ability to reduce the nociception (Table II) that can contribute to oxidative stress modulation. Evidence that pain can induce the increase of oxidative stress, as a physiological response to the nociceptive process exists [26]. Co-administration of EGCG and MC results in improving the oxidative stress/antioxidant status parameters and the nociceptive process, the most efficient results being obtained for L-EGCG administration.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism involved in these results could be mediated by its ability to reduce the nociception (Table II) that can contribute to oxidative stress modulation. Evidence that pain can induce the increase of oxidative stress, as a physiological response to the nociceptive process exists [26]. Co-administration of EGCG and MC results in improving the oxidative stress/antioxidant status parameters and the nociceptive process, the most efficient results being obtained for L-EGCG administration.…”
Section: Resultsmentioning
confidence: 99%
“…There are several publications in the literature describing the pathophysiological connection between oxidative stress levels and pain. One study indicated that oxidative stress could trigger pain pathways through glutamatergic signaling and activation of inflammatory reactions, as well as by directly affecting nociceptive centers in the brain (Perrone et al, 2017). In another study, it was mentioned that oxidative stress may cause peripheral sensitization; that is, it can change nociception that may cause hyperalgesia (Nashed et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…is preferred as a non-pharmacological alternative due to the proven in clinical neonatological and pediatric practice in the treatment of traumas with hematomas, open wounds, fractures, headache and other conditions accompanied by varying degrees of pain. [21,22]. In addition, Arnica, administered orally in homeopathic dilutions, showed positive clinical effects in the suppression of post-operative pain, edema and ecchymosis.…”
Section: Discussionmentioning
confidence: 99%